Parametric study of a two-shaft gas turbine cycle model of power plant - Ibrahim, Thamir K.; M. M., Rahman (IOP Publishing, 2012)
In this paper, the parametric study of a two shafts gas turbine cycle model of the power plant was proposed. The power output, compression work, specific fuel consumption and thermal efficiency are evaluated with respect to the cycle temperature and compression ratio for a typical set of operating conditions. Two shafts gas turbine cycle with realistic parameters is modeled. The computational model was developed utilizing the MATLAB codes. Turbine work found to be decreases as ambient temperature increases as well as the thermal efficiency decreases. It can be seen that the thermal efficiency and power output increases linearly with increases of compression ratio while decreases of ambient temperature. The power of the simulated two shafts gas turbine reach to 135MW, which is higher than the simple gas-turbine cycle (Baiji gas turbine power plant, power < 131MW). The specific fuel consumption increases with increases of ambient temperature as well as the lower turbine inlet temperature. Even though at the lower turbine inlet temperature is decrement the thermal efficiency dramatically and the power output increases linearly with increases of compression ratio and decreases the ambient temperature.